The fictional world of William Hoffman - Frank, William L., 1929- (University of Missouri Press, 2000)
"Over the past forty-five years, William Hoffman has written eleven novels, including the critically acclaimed Tidewater Blood, winner of the Dashiell Hammett award, and four short-fiction collections, the most recent being Doors - all of which have enjoyed a loyal and appreciative readership." "The Fictional World of William Hoffman provides readers with the first assessment of Hoffman's work. Including commentary and analysis from fellow writers as well as from established and emerging critics this collection of essays aims to deepen the appreciation of those already familiar with Hoffman and to introduce new readers to one of the South's most influential voices."--Jacket